Exploring The Impact of Technology in Enhancing English Reading Skill - L. M. Alfan Fawaizul Ihsani; M. Tanwirul Hasani; M. Al Farabi Akma; Jupilatun Jupilatun; Selamet Riadi Jaelani (LPPM Politeknik Pratama, 2023)
This study aimed to explore the impact of technology in enhancing English reading skills at the sixth semester of English education at universitas hamzanwadi. This study used a qualitative descriptive design taken by purposive sampling. There are 34 participants of this study. Observation, interview, and documentation is used to gather the data. The result of the observation showed that mostly of students are comfortable to use the new technology to increase reading skills. It is because of the new era that needs technology to learn. It is supported by the result of interview. The students said that it is easier to use e-book than books because it can apply by phone and so on. Additionally, the documentation is used to add the information from observation and interview. In conclusion, technology gives a good impact to increase students’ ability in reading skills.